Pendidikan Multikultural dalam Pengembangan Kreativitas Peserta Didik melalui Program P5 - Khafidhotun Nasikhah (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
This study aims to determine multicultural education carried out through the Pancasila student strengthening program and is based on the culture of students who are known to come from various regions in Indonesia in honing creativity. The conditions of students from various regions are diverse, especially reflected in their language, attitudes, and how they socialize, this is reflected in SMKS Al-Mahrusiah Lirboyo. This study uses a qualitative descriptive method with data sources from the principal, curriculum representative, and students in grades X and XI by taking 5 classes each with a total of 403 students. The data collection technique was carried out by in-depth interviews, documentation, observation. While the data analysis was carried out by data collection, data reduction, data presentation, and data verification. Data from observations and in-depth interviews with curriculum representatives, principals, teachers, and students have implemented multicultural education, it turns out that in the process of implementing P5 kumer it can create honing creativity. In the themes "build the soul and body" and "work", from both themes students are required to learn contextually. Through these activities, an attitude of mutual respect for differences, understanding the diversity of regional cultures, respecting social status, and being able to reflect back on the identity of the nation is reflected. Multicultural education from P5 is realized as a journey process that is able to bring students to hone their creativity. for example in the theme 1) build the soul and body: making 3D wall magazines related to the archipelago combined with presentations based on creations, regional dances, regional foods, and regional songs, depending on the theme of the wall magazine created; 2) work: processing used goods into usable goods, with different creations and making canva power points with various creations and innovations. Thus, multicultural education through P5 activities can be a bridge to hone students' creativity.